Criminal Liability for "Photographic Piracy"? - Spencer, JR (Victoria University of Wellington Law Review, 2023)
The author is a Professor Emeritus of Cambridge University, where for many years Tony Smith was his friend and valued colleague. In this article he critically analyses the existing law in relation to taking or publishing photographs of other people without their consent and considers the desirability of extending criminal liability for such behaviour by the creation of a new criminal offence.